1/20,000th of a Person? Democracy and Protecting Equal Rights in Notice and Comment Rulemaking - Cantalupo, Nancy Chi (Columbia Journal of Gender and Law, 2024)
Notice-and-comment rulemaking is a key function of the U.S. administrative state, thought to give members of the public access to the process of government decisionmaking. However, notice-and-comment rulemaking fails to accomplish that goal, and its deficiencies have critical implications for U.S. democracy and for the role of women and other traditionally underrepresented groups in that democracy. This Article examines the many ways in which notice-and-comment rulemaking has fallen short of its central purpose through a case study of a 2018–19 rulemaking dealing with enforcement of Title IX’s prohibition on sexual harassment. Members of the public, mobilized by activists, filed a historic 124,000+ comments in that rulemaking. This author created and led a “crowd-research” innovation to catalog ninety-four percent of those comments. Analysis of that rulemaking and its comments exposes rulemaking’s oligarchic tendency to value technocratic practices above democratic ones, a tendency that is particularly problematic in the case of rulemakings that implicate civil rights and discrimination. This Article proposes a path for agencies to avoid notice-and-comment rulemaking’s failings by supplementing traditional processes with a modified form of negotiated rulemaking.